Penerapan Good Manufacturing Practices (GMP) pada Industri Pangan Skala Kecil Bakso Ikan - Febri; Apriani, Ayu; Lugeri, Leo; Siskawanti, Fitriya; Kurniasari, Megawati (PAKIS JOURNAL INSTITUTE, 2024)
This research examines the implementation of Good Manufacturing Practices (GMP) in small-scale food industries, focusing on a fish ball processing business in Pemangkat District, West Kalimantan. The research methodology includes field observations and interviews to evaluate GMP aspects such as production site conditions, sanitation facilities, equipment, employee hygiene, storage and labeling, and process control. The results indicate that GMP implementation in this business still requires significant improvements in various aspects. The production site does not meet cleanliness and layout standards. Sanitation facilities are far from adequate, with a lack of proper handwashing facilities and improper waste management. Production equipment, though complete, shows signs of corrosion and lack of maintenance. Employee hygiene practices are inconsistent, including the use of personal protective equipment. The product storage and labeling system is not well-organized and does not meet regulatory standards. The absence of written Standard Operating Procedures (SOPs) and consistent monitoring systems for each stage of the production process is also a weakness. This study concludes that comprehensive improvement efforts in GMP implementation are necessary to enhance the safety and quality of the fish ball products produced.